2020
DOI: 10.1016/j.matt.2020.06.026
|View full text |Cite
|
Sign up to set email alerts
|

High-Density Planar-like Fe2N6 Structure Catalyzes Efficient Oxygen Reduction

Abstract: A planar-like Fe 2 N 6 structure with distinguished catalytic mechanism was highlighted as a high-efficiency oxygen reduction catalyst. Accelerated catalytic kinetics and highly suppressed side reaction enabled the planar-like Fe 2 N 6 structure to exhibit over 700% increase in mass activity than traditional isolated iron-nitrogen sites. Proton-exchange membrane fuel cells built with this catalyst also achieved a large peak power density of 845 mW cm À2 , representing a critical breakthrough for the practical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
164
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 207 publications
(173 citation statements)
references
References 41 publications
9
164
0
Order By: Relevance
“…Meanwhile, the higher white line intensity of FeNi SAs/NCs also confirms that Fe is more positively charged and indicates a strong interaction between the heteronuclear Fe‐Ni atoms and the defective nitrogen‐doped carbon matrix. [ 32,41 ] Moreover, the variation trend of the white line intensity is consistent with that of the M‐N/O coordination number, and the enhanced white line intensity can be attributed to the increased percentage of single atomic and proposed single atomic structures, further demonstrating that atomic‐level metal structures can effectively adjust the properties of electrons. In the k 3 ‐weighted Fourier transform (FT)‐EXAFS spectra in the R‐space (Figure 2d), as expected, FeNi SAs/NC exhibits two strong peaks at 1.50 and 2.27 Å, corresponding to Fe‐N and metal–metal bonds, respectively.…”
Section: Resultssupporting
confidence: 52%
“…Meanwhile, the higher white line intensity of FeNi SAs/NCs also confirms that Fe is more positively charged and indicates a strong interaction between the heteronuclear Fe‐Ni atoms and the defective nitrogen‐doped carbon matrix. [ 32,41 ] Moreover, the variation trend of the white line intensity is consistent with that of the M‐N/O coordination number, and the enhanced white line intensity can be attributed to the increased percentage of single atomic and proposed single atomic structures, further demonstrating that atomic‐level metal structures can effectively adjust the properties of electrons. In the k 3 ‐weighted Fourier transform (FT)‐EXAFS spectra in the R‐space (Figure 2d), as expected, FeNi SAs/NC exhibits two strong peaks at 1.50 and 2.27 Å, corresponding to Fe‐N and metal–metal bonds, respectively.…”
Section: Resultssupporting
confidence: 52%
“…Zhang et al also reported that Fe 2 N 6 was more active than FeN 4 in catalyzing ORR. [142] Table 1 summarizes the activity of various SACs for 2e − and 4e − ORR.…”
Section: Dual Metal Active Centermentioning
confidence: 99%
“…The oxygen reduction reaction (ORR), represents the cornerstone for regenerative energy conversion devices involving polymer electrolyte membrane fuel cell (PEMFC) and metal–air batteries 1 7 . Hitherto, the generally recognized state-of-the-art platinum (Pt)-based catalysts possess the highest kinetic activity in catalyzing ORR under acid and alkaline media, however, the scarcity, price, and low methanol crossover tolerance of Pt alloys have motivated the search for cost-effective non-noble-metal electrocatalysts 8 13 .…”
Section: Introductionmentioning
confidence: 99%